การปรับปรุงระบบบริหารห้องปฏิบัติการทดสอบคุณสมบัติเชิงกลของแผ่นเหล็กรีดเย็น - ศศิธร อิ่มเงิน (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The objective of this research is to improve laboratory management system and reduce errors of factors affecting the mechanical testing of cold rolled steel sheet which applying the general requirements of ISO / IEC 17025:2005 for the competence of testing and calibration laboratories as a guidance. Laboratory has found that incomplete requirement from the current testing 9 from 15 management requirements and 4 from 10 technical requirements. After that we analyzed the problem by dividing into two main problems. First management system problems have been improved by creating and revising standards to support each requirement. Secondary testing machine and methods problems have been solved. According to tests to ensure the quality of cold rolled sheet steel, hardness tests showed that the frequency of the most active average 2,025 per month. And most problems of data collection in Jan-Mar’08 were caused by abnormal test average 38 times / month or 1.87% / month. After analyzing the data was caused by the test error 1.13% per month and recording of testing result wrong 0.44% / month. The both factors were selected to the improvement of hardness testing. To reduce these problems, standard procedures were developed by apply ISO / IEC 17025:2005 to validation testing methods and verification testing machines. Estimation of the uncertainties of measurement, measurement system analysis, evaluation of the laboratory proficiency testing and application of control chart tracking disorders were analyzed by regular testing. Result of improved testing process, has been reduced errors by testing down from 1.13% to 0.32% / month and save the test results from 0.44% to 0.02% per month